Public Sector Governance in Australia - Edwards, Meredith (ANU Press, 2012)
Australia lacks a scholarly book that covers recent developments in public sector governance in Australia and blends cross-disciplinary perspectives from law, management, public administration and public policy. The primary reason for writing this book is to fill the gap in the treatment of this subject, and to provide insights from empirical evidence and current practice. The book provides the first comprehensive theoretical and empirical work on governance in the Commonwealth public sector. It addresses the issues that emerged under the Howard government as well as their handling under the Rudd and Gillard governments. The book aims to enhance understanding of and communication about public governance across government, industry and the community. The authors bring to this book expertise gained from political science, public administration and policy, public and private sector law.